1991
DOI: 10.1088/0031-8949/43/5/005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental stark widths of xenon II spectral lines

Abstract: Stark widths of many prominent 6s-6p and 5d-6p transitions have been measured and compared with theoretical results. A high current pinched discharge was used as a spectroscopic source. Electron density and temperature were estimated in 2.65 x 1022m--3 and 1.45 x 104K respectively.Experimental Stark widths agree well with previous theoretical results.Our data are compared with those of other authors concerning to the homologous ions Ne 11, Ar 11, Kr I1 and Xe 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
4
18
2
Order By: Relevance
“…Our theoretical results are in excellent agreement as well with the experimental values of Vitel & Skowronek (1987) and Konjević & Uzelac (1990). The agreement with Manola et al (1988), Lesage et al (1989), Bertuccelli et al (1991) and Gigosos et al (1994) is also within the error bars of theory and experiment. For 6p−6d transitions there exist only experimental data by Lesage et al (1989) and Gigosos et al (1994).…”
Section: Results and Discusionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our theoretical results are in excellent agreement as well with the experimental values of Vitel & Skowronek (1987) and Konjević & Uzelac (1990). The agreement with Manola et al (1988), Lesage et al (1989), Bertuccelli et al (1991) and Gigosos et al (1994) is also within the error bars of theory and experiment. For 6p−6d transitions there exist only experimental data by Lesage et al (1989) and Gigosos et al (1994).…”
Section: Results and Discusionsupporting
confidence: 86%
“…The values obtained for temperatures from 5000 K up to 50000 K and an electron density of 10 23 m −3 are compared (in Table 2 and in Figs. 1-4) with the available experimental data Miller et al 1981;Richou et al 1984;Nick & Helbig 1986;Vitel & Skowronek 1987;Manola et al 1988;Lesage et al 1989;Di Rocco 1990b;Konjević & Uzelac 1990;Bertuccelli et al 1991;Gigosos et al 1994). Since we found that the ion broadening contribution is about several per cent, only the electron broadening contribution is given.…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) vary for about ±40% around the average value. There are only a few results from Miller et al (1982) and Bertuccelli et al (1991a) that are too high. The Xe II halfwidth results corresponding to 6p−6d transitions (Fig.…”
Section: Analysis Of the Stark Halfwidthsmentioning
confidence: 99%
“…Several works (Lesage et al 1981;Miller et al 1982;Richou et al 1984;Nick & Helbig 1986;Pittman & Konjević 1986;Vitel & Skowronek 1987;Manola et al 1988;Lesage et al 1989;Di Rocco 1990a;Di Rocco 1990b;Konjević & Uzelac 1990b;Bertuccelli et al 1991a;Bertuccelli et al 1991b;Bertuccelli & Di Rocco 1993;Gigosos et al 1994;Djurović et al 2006;Cirišan et al 2007) are devoted to investigations of singly ionized xenon, while others (Konjević & Pittman 1987;Iriarte et al 1997;Romeo et al 1998;Seidel et al 2001;Peláez et al 2006;Cirišan et al 2007) deal with doubly ionized xenon. In the papers Konjević et al (1984), Konjević & Wiese (1990a), Konjević et al (2002), and Lesage (2009), critical reviews of the published experimental results are given.…”
Section: Introductionmentioning
confidence: 99%